Developing a new immunoPET tracer with Phage Display Technology to Target the Alpha-1 Subunit of the GABA-A Receptor - Chaar, Niina (My University, 2023)
Schizophrenia is a debilitating psychiatric condition affecting one in seven individuals worldwide (Mcgrath et al., 2008). Currently, there is no brain imaging method for the direct diagnosis of this disorder. PET utilizes high affinity radiotracers which target unique molecular markers in the brain. However, existing PET research in schizophrenia has focused on glucose metabolism and dopamine dysfunction, whilst the role of GABA and its receptors is still poorly understood. In vivo PET studies and ex vivo autoradiography studies show contradictory results regarding the distribution of GABAergic neurons (Beneyto et al., 2011; de Jonge et al., 2017; Taylor & Tso, 2015). This gap in current knowledge can be eliminated with the development of new radiotracers which bind to the receptor subunits, instead of the dual-subunit binding which many current tracers utilize do. Understanding the receptor distribution patterns throughout the brain could lead to a new and much needed method of schizophrenia diagnosis through PET imaging. In this thesis project, immunoPET and phage display technology were used to successfully create Fab (fragment, antigen-binding) antibodies which target the alpha-1 subunit of the GABA-A receptor (Smith & Petrenko, 1997). High throughput screening of a large pool of engineered antibodies was used to find high affinity Fabs towards the target. Previously enriched scFv libraries were converted into Fab format and enriched either against a mammalian cell line overexpressing the target, GABA-A alpha-1 subunit, or magnetic beads coated with the target peptide. The success with magnetic bead enrichment allowed for subsequent immunoassay screenings to detect the best alpha-1 binders. The development of these Fab antibodies targeting a subunit of the GABA receptor is the first step to paving the way for the development of a new radiotracer to improve our understanding of the pathophysiological mechanisms behind the GABAergic system an its role in schizophrenia and other related diseases.
Keywords: phage display, schizophrenia, GABA-A alpha-1 subunit, Fab, immunoPET, mammalian cell culture, magnetic beads